2019
DOI: 10.3390/cancers11040529
|View full text |Cite
|
Sign up to set email alerts
|

Role of Macrophage Migration Inhibitory Factor (MIF) in Melanoma

Abstract: Macrophage migration inhibitory factor (MIF) is an inflammatory cytokine involved in the carcinogenesis of many cancer types. Here, we review the published experimental and clinical data for MIF and its involvement in melanoma. All reported data show that MIF is overexpressed in melanoma cells, especially in case of metastatic disease. Clinical studies also indicate that high MIF expression is positively associated with aggressiveness of the disease. Some data also highlight the implication of MIF in angiogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 47 publications
(102 reference statements)
1
50
0
Order By: Relevance
“…MIF may also contribute to immunoinflammatory events during development of Duchenne s syndrome [37] and seems to play a pathogenetic role in major depressive disorders [38]. More recent studies also indicate that MIF is implicated in certain forms of cancer phenotypes such as melanoma, glioblastoma, prostate cancers, and neuroblastoma [39][40][41][42][43][44][45].…”
Section: Biology Physiology and Physiopathology Of Mifmentioning
confidence: 99%
“…MIF may also contribute to immunoinflammatory events during development of Duchenne s syndrome [37] and seems to play a pathogenetic role in major depressive disorders [38]. More recent studies also indicate that MIF is implicated in certain forms of cancer phenotypes such as melanoma, glioblastoma, prostate cancers, and neuroblastoma [39][40][41][42][43][44][45].…”
Section: Biology Physiology and Physiopathology Of Mifmentioning
confidence: 99%
“…We and others have shown that MIF and DDT are involved in several diseases of different origins such as immunoinflammatory and autoimmune diseases, neurodegenerative and neuropsychiatric diseases, and cancer [24][25][26][27][28][29][30][31].…”
Section: Mif and Cancermentioning
confidence: 99%
“…In addition, evidence generated during the last 15 years has also supported a pro-oncogenic role of MIF in certain types of cancers [29][30][31]. MIF may upregulate several tumorigenic processes, including tumor growth, invasiveness, and angiogenesis [32] primarily, but not exclusively, through its angiogenetic action, its AKT mediated antiapoptotic effects, and the inhibition of p53 function.…”
Section: Mif and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The macrophage migration inhibitory factor (MIF) is synthesized by epithelial and endothelial cells, T lymphocytes, macrophages, and by several tumors, particularly melanoma (35,36). MIF exerts its oncogenic effects through binding to CD74 receptor, CXCR4 chemokine receptor, and CD44, involved in MIF cellsignaling (37).…”
Section: Direct Binding Of Rb9 Peptide To Mif and Cd74 Proteinsmentioning
confidence: 99%